2014
DOI: 10.1186/1880-5981-66-114
|View full text |Cite
|
Sign up to set email alerts
|

Seismic velocity structure in and around the Naruko volcano, NE Japan, and its implications for volcanic and seismic activities

Abstract: Geofluids is important for understanding volcanic and earthquake generation processes. In this study, we obtained a detailed seismic velocity structure in and around the Naruko volcano, northeastern Japan, using data from a dense seismic observation network. We found a distinct seismic low-velocity zone (LVZ) beneath the Naruko volcano, with a diameter of nearly 10 to 20 km in the lower crust. This LVZ could correspond to a magma chamber. We also found a seismic low-velocity zone beneath the aftershock region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 31 publications
2
44
0
Order By: Relevance
“…At greater depths, the LVZs beneath Naruko Volcano and Onikobe Caldera shift southwestward and southward, respectively. While the distinct LVZ beneath Onikobe Caldera has been recognized in previous studies (e.g., Nakajima and Hasegawa 2003;Okada et al 2014), the LVZ beneath Naruko Volcano had previously been resolved only by a magnetotelluric survey (Ogawa et al 2014). We also found a LVZ beneath Mt.…”
Section: Methodssupporting
confidence: 50%
See 2 more Smart Citations
“…At greater depths, the LVZs beneath Naruko Volcano and Onikobe Caldera shift southwestward and southward, respectively. While the distinct LVZ beneath Onikobe Caldera has been recognized in previous studies (e.g., Nakajima and Hasegawa 2003;Okada et al 2014), the LVZ beneath Naruko Volcano had previously been resolved only by a magnetotelluric survey (Ogawa et al 2014). We also found a LVZ beneath Mt.…”
Section: Methodssupporting
confidence: 50%
“…This LVZ extends approximately 15 km southward at depths of 5 and 7 km. The LVZs in the south and southeast correspond to a sedimentary basin as mentioned in Okada et al (2014). To discuss the LVZs mentioned above, we compared our results with the distribution of aftershocks of the 2008 earthquake and S-wave reflectors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional (3D) seismic velocity heterogeneities have enhanced our understanding of spatial variations in the elastic properties beneath high-strain-rate zones (e.g., Nakajima and Hasegawa 2007;Okada et al 2014). However, the anelasticity associated with such zones is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…They found a southward-dipping, sub-vertical conductor that may imply the presence of geofluids just below the volcano. Okada et al (2014) found seismic low-velocity zones beneath the same volcano and in the aftershock region of the 2008 Iwate-Miyagi Nairiku earthquake, both of which can be attributed to the presence of geofluids. The former, having a diameter of 10 to 20 km, resides in the lower crust.…”
Section: Geofluids Detected With Magnetotelluric and Seismic Observatmentioning
confidence: 99%